PERIPHERAL PARALYSIS OF THE FACIAL NERVE AS A MANIFESTATION OF NEUROENDOCRINE TUMOR OF THE MIDDLE EAR – CASE REPORT - Miljković, Ana (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: Acute idiopathic peripheral facial nerve paralysis is often linked to viral infections such as Herpes simplex virus type 1 reactivation. Neuroendocrine tumors (NETs) of the middle ear (MEANT) are rare and present with non-specific symptoms, including hearing loss, otalgia, and neuropathy, complicating early diagnosis. Case report: Report the case of a 47-year-old patient treated for chronic otitis since 2020. In 2024, the onset of peripheral facial nerve paralysis prompted advanced diagnostics, including MRI, CT, biopsy, and immunohistochemical analyses, confirming MEANT. Treatment included surgical excision, gamma knife therapy, and regular tumor marker monitoring. A delayed diagnosis of the tumor highlighted the need for heightened clinical suspicion in cases of chronic ear pathology with atypical progression. Conclusion: Neuroendocrine tumors of the middle ear are diagnostic and therapeutic challenges due to their rarity and non-specific presentation. Early recognition of peripheral facial nerve paralysis as a potential indicator of an underlying malignancy is critical. Multidisciplinary management, integrating advanced imaging, histopathological confirmation, surgical intervention, and adjuvant therapies, improves outcomes and minimizes relapse risks. General practitioners play a pivotal role in identifying early symptoms to reduce diagnostic delays.